The Environmental Law Enforcement In The Crime Of Forest Damage - Erlia Hendrasta; Achmad Sulchan (Universitas Islam Sultan Agung, 2021)
This study aims to determine and analyze environmental law enforcement in criminal acts of forest destruction during the Covid-19 pandemic. The approach method used is normative juridical research. The results of the study show that although the Covid-19 pandemic period is also very influential, the law enforcement process must still be carried out. One of the policies adopted by using teleconference technology. Not all trials are held virtually, the judge chooses and determines which cases can be carried out via video conference. For cases that are easy to prove, such as narcotics arresting hands, carrying sharp weapons and others. But for cases such as cases of fraud, murder and others held face to face. Virtual hearings are more suitable for reading indictments or charges. Meanwhile, the examination of witnesses is carried out face-to-face.